Simulation of failure in timber with structural inhomogeneities using an automated FE analysis. (September 2018) - Jenkel, C.; Kaliske, M.
Highlights: A geometrical modelling procedure for timber containing knots based on experimental measurements is presented. Two algorithms for an automated FE modelling, the Regular Meshing and the Streamline Meshing, are introduced. The grain course is modelled numerically by means of the Streamline Approach. The automation of the procedure for the use in numerical timber grading is demonstrated. Elastic, plastic and brittle failure analyses of real timber boards are shown. Abstract: In this contribution, approaches to analyse timber characterized by structural inhomogeneities are introduced using the Finite Element Method (FEM). In an automatable procedure, the structural behaviour of timber containing knots is simulated on the basis of a few geometrical data obtained by surface scans. To generate FE models automatically, two meshing procedures are introduced. The fibre course is determined numerically using a flow-grain analogy. Elastic, plastic and fracture mechanically based macroscopic material models are used to represent the mechanical properties of homogeneous wood, free of inhomogeneities. The procedure is used to compute global material parameters, as the global longitudinal elasticity modulus and tensile strength similar to EN 338 and therefore can be used for numerical timber grading. For comparison, experiments are considered where the global elasticity modulus and the ultimate load have been determined in tensile tests. The tests are simulated for selected boards. Possible failure zones are identified by the application of plasticity models. To determine the ultimate load at tensile loading numerically, cohesive elements are applied.